Il linguaggio senza coscienza di Shakespeare: una rilettura del monologo dell’Amleto - Rocchi, Ilaria (Il sogno della farfalla, 2017)
The aim of this study is to propose a new interpretation of the famous Shakespearean monologue “To be or not to be”. Moving away from the conceptual approach critics offered in the last century, the author explores the universal ability of Shakespearean language to convey meaning through images. Starting from a linguistic, etymological and translational analysis, the author conceives a new interpretation which she draws directly from images arising from the text. In this research, metaphors and rich poetic imagery become the gateway to a deeper understanding of the character’s internal thoughts and feelings. In contrast with a rather religious and metaphysical perspective, the author outlines the undamental elements that emerge in the monologue, such as the role of dreams and conscience in human beings’ life.